A imperatriz Teodora e Antonina: a atuação feminina no poder imperial a partir das obras História Secreta e História das Guerras de Procópio de Cesareia - Santos, Aylla Maria Alves dos (2024)
Among the writings of Late Antiquity, the work of Procopius of Caesarea stands out for addressing the wars waged by Emperor Justinian (527-565) against the Persians, the Ostrogoths and the Vandals. In addition to the military campaigns, his work known as History of the Wars, composed of eight books, addresses some of the moments that marked Justinian's government, such as the Nika Revolt and the Plague that devastated Constantinople. He also wrote Buildings and Secret History, the latter, written in the rhetorical genre inventio, Procopius of Caesarea recounts the backstage of the military campaigns of general Belisarius, which he accompanied as an advisor. Full of criticism, the book shows the author's discontent with the attitudes of Justinian and Belisarius, who according to him, influenced by their respective wives, Empress Theodora and Antonina, caused the Roman ruin. In this sense, considering the emphasis on these women in the procopian narrative, and their involvement in the imperial procedures, we intend in this research to analyze the roles of Empress Theodora and Antonina in the Imperial Power from Secret History and History of the Wars, observing the dissimilarities and similarities that can be perceived in these works.